Avaliação do desempenho de cultivares de alface em sistema hidropônico - Henrique, Allan Gabriel Soares (Universidade Federal de São Carlos, 2020)
This paper’s main goal was to evaluate the performance of different lettuce cultivars in a hydroponic cultivation system. The lettuces were divided in two groups, "crespa" and "americana", where the cultivars Milena, Palmas, Gran Rapids, Lucy Brow, Delicia Americana and Mayumi were studied. The lettuce seedlings were cultivated in 288 cell trays in a protect environment. The experiment took place in Piraju – SP, in the production area in Chácara Pingo de Ouro. After the seedling production, the plants were transplanted to the nursery stage, where they stayed for 14 days until the transplantion to the final stage and then harvest. After the harvest, the number of leaves, total weight of fresh mass, length and total weight of the roots’ fresh mass and stalk length were measured. Then it was possible to realize that the cultivars of crespa’s group were superior in number of leaves, and Milena and Palmas varieties stood out. The stalk length of the varieties of americana’s group was lower than crespa’s group, specially the Lucy Brown variety. The roots length of the cultivars Milena and Lucy Brow showed the biggest length, and both were statistically equal. The last evaluated variable, the fresh mass of aerial part, the Lucy Brown variety was superior than the others, weighing on average 416,6 grams, followed by Palmas from crespa’s group, 407,0 grams.
Evaluation of the performance of different lettuce cultivars in hydroponic system
Keywords: Cultivo hidropônico; Lactuca Sativa; Comparação de desempenho; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA